2023
DOI: 10.1021/jacs.2c12006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of *CHxO Adsorption to Facilitate Electrocatalytic Reduction of CO2 to CH4 over Cu-Based Catalysts

Abstract: Copper (Cu) can efficiently catalyze the electrochemical CO2 reduction reaction (CO2RR) to produce value-added fuels and chemicals, among which methane (CH4) has drawn attention due to its high mass energy density. However, the linear scaling relationship between the adsorption energies of *CO and *CH x O on Cu restricts the selectivity toward CH4. Alloying a secondary metal in Cu provides a new freedom to break the linear scaling relationship, thus regulating the product distribution. This paper describes a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…(c) CH 4 FEs at −1.18 V (vs RHE) on Pd, Pd 7 @Cu 1 , Pd 7 @Cu 2 , Pd 7 @Cu 3 , and Cu. (d) Comparison of this work with previous studies on the electrocatalytic CO 2 -to-CH 4 reaction in 1 M KOH by a flow cell device (refs ). (e) Potential versus time of Pd 7 @Cu 2 at a constant current density of 100 mA·cm –2 and the corresponding CH 4 FE.…”
Section: Resultsmentioning
confidence: 80%
“…(c) CH 4 FEs at −1.18 V (vs RHE) on Pd, Pd 7 @Cu 1 , Pd 7 @Cu 2 , Pd 7 @Cu 3 , and Cu. (d) Comparison of this work with previous studies on the electrocatalytic CO 2 -to-CH 4 reaction in 1 M KOH by a flow cell device (refs ). (e) Potential versus time of Pd 7 @Cu 2 at a constant current density of 100 mA·cm –2 and the corresponding CH 4 FE.…”
Section: Resultsmentioning
confidence: 80%
“…2(a)) have been successfully demonstrated as CO 2 RR catalysts in the experiment, the Co–N–M dual sites may enable the adsorbed *CHO at the Co site to facilely migrate to the M site with or without PCET via a short-distance bridge bonding style or assisted bonding with bridge-N, thereby promoting the *OCH 2 formation through an inner tandem reaction. 34–36 Considering that the binding affinity of the O atom in *OCH 2 is closely related to the metal d electrons, we chose six 3d metals (Cr, Mn, Fe, Co, Ni, and Cu) with various d electron numbers to construct Co–N–M dual sites. According to the previous report on the experimental synthesis of Co–N–M dual sites, the geometric structures of Co–N–M catalysts were built as Co–N–M–N 6 moieties into the superlattice of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…117 Zhao et al reported that the oxophilic metal (La) was able to modulate the catalytic activity of Cu, improving the CH 4 selectivity (up to 64.5%), which was approximately 7.8 times higher than for Cu. 118 Infrared spectroscopy and DFT theoretical calculations showed that the presence of La would lead to stronger *CH x O adsorption and promote the cleavage of C–O for *CH 3 O, thus increasing the proportion of CH 4 in the products.…”
Section: Electronic Structural Modulationmentioning
confidence: 99%